Experimental study on exterior precast RC beam to CECFST column joint under lateral cyclic loading - Ho, Brandon Lye Kiat (Nanyang Technological University, 2023)
Beam-column joints (BCJ) play an integral role in the reinforced concrete (RC) frame structure. However, due to high seismic design requirements, there is high complexity in reinforcement detailing which results in congested reinforcement and difficulty in the prefabrication and construction process in regions with high earthquake intensity.